Tuning LiBH4 for hydrogen storage: Destabilization, additive, and nanoconfinement approaches - Puszkiel, Julián Atilio (2020)
Hydrogen technology has become essential to fulfill our mobile and stationary energy needs in a global low-carbon energy system. The non-renewability of fossil fuels and the increasing environmental problems caused by our fossil fuel-running economy have led to our efforts towards the application of hydrogen as an energy vector. However, the development of volumetric and gravimetric efficient hydrogen storage media is still to be addressed. LiBH4 is one of the most interesting media to store hydrogen as a compound due to its large gravimetric (18.5 wt.%) and volumetric (121 kgH2/m3) hydrogen densities. In this review, we focus on some of the main explored approaches to tune the thermodynamics and kinetics of LiBH4: (I) LiBH4 + MgH2 destabilized system, (II) metal and metal hydride added LiBH4, (III) destabilization of LiBH4 by rare-earth metal hydrides, and (IV) the nanoconfinement of LiBH4 and destabilized LiBH4 hydride systems. Thorough discussions about the reaction pathways, destabilizing and catalytic effects of metals and metal hydrides, novel synthesis processes of rare earth destabilizing agents, and all the essential aspects of nanoconfinement are led.